2007
DOI: 10.1073/pnas.0607514104
|View full text |Cite
|
Sign up to set email alerts
|

Protection against inflammation- and autoantibody-caused fetal loss by the chemokine decoy receptor D6

Abstract: Fetal loss in animals and humans is frequently associated with inflammatory conditions. D6 is a promiscuous chemokine receptor with decoy function, expressed in lymphatic endothelium, that recognizes and targets to degradation most inflammatory CC chemokines. Here, we report that D6 is expressed in placenta on invading extravillous trophoblasts and on the apical side of syncytiotrophoblast cells, at the very interface between maternal blood and fetus. Exposure of D6 ؊/؊ pregnant mice to LPS or antiphospholipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
207
2
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(222 citation statements)
references
References 36 publications
(50 reference statements)
10
207
2
3
Order By: Relevance
“…Thus, a simple model emerges whereby chemokine scavenging by D6 in vivo suppresses inflammatory leukocyte recruitment by reducing chemokine levels. Consistent with this model, elevated levels of bioavailable D6-binding chemokines are observed in inflamed D6 null mice (7)(8)(9)(10)(11).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Thus, a simple model emerges whereby chemokine scavenging by D6 in vivo suppresses inflammatory leukocyte recruitment by reducing chemokine levels. Consistent with this model, elevated levels of bioavailable D6-binding chemokines are observed in inflamed D6 null mice (7)(8)(9)(10)(11).…”
supporting
confidence: 63%
“…Resolution is aided by D6, a 7TMR related to CCR1-5, which binds 12 of the chemokine ligands for these receptors (4,5) and is expressed, at least in humans, by lymphatic endothelial cells, trophoblasts, and some leukocyte populations (6,7). D6 null mice show prolonged exaggerated responses to cutaneous inflammatory stimuli and tumor induction (8 -10), enhanced leukocyte infiltration during allergic lung inflammation (11), and increased sensitivity to experimentally induced fetal resorption (7). Conversely, epidermal D6 transgene expression suppresses cutaneous inflammation and tumorigenesis (10).…”
mentioning
confidence: 99%
“…Data from several groups suggest that the decoy chemokine receptor D6 may a play critical role in controlling leukocyte infiltration by binding to and sequestering inflammatory chemokines in the skin, particularly those that bind to CCR1-5 (22). D6 is unlikely to sequester CCL27, however, because heterologous radioligand displacement experiments have suggested that D6 does not bind to CCL27 (R. Nibbs and G. Graham, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ/Ϫ mice have demonstrated that its chemokine scavenging activity attenuates the severity of inflammation in different experimental models (12,(15)(16)(17) and suppresses inflammation-driven tumor development (18) (19).…”
mentioning
confidence: 99%
“…D6, the best described chemokine decoy receptor (6), is a constitutively internalizing receptor expressed by lymphatic endothelial cells (11), trophoblast cells (12), and, at lower levels, some leukocyte subsets (13). D6 selectively recognizes and degrades most inflammatory CC chemokine agonists of CCR1 to CCR5 (10).…”
mentioning
confidence: 99%